Comparison of Hospital Consultation and Summer Camp Lifestyle Intervention Programs for Sustained Body Weight Loss in Overweight/Obese Greek Children - Anna L. Papageorgiou; Vasiliki Efthymiou; Aikaterini Giannouli; Paraskevi Xekouki; Christina C. Kranioti; George P. Chrousos (MDPI AG, 2022)
Two lifestyle intervention programs of a health initiative named "Evrostia" were conducted at (a) an outpatient obesity clinic of a children's hospital and (b) summer camp (SC), respectively. Thirty overweight/obese children were randomly selected to participate in each intervention arm to assess the efficacy of the SC intervention and its possible superiority over usual hospital consultation (HC) practice. There was a statistically significant decrease in body weight (BW), and body mass index (BMI) in both programs. A higher duration of reduced BW was observed in the SC compared to HC intervention. Regarding the nutritional behavior, there was a significant increase in the consumption of breakfast, fruit and vegetables, and a reduction in the consumption of beverages and sweets in the SC group. A significant increase in the hours of weekly physical activity was also observed in children of the SC program. The comparison between the two lifestyle intervention programs showed that the SC program improved nutritional behaviors and physical activity and promoted longer preservation of BW loss than that of the HC program. Thus, the holistic and experiential approach of the SC program was more successful in the treatment of overweight and obesity in children than a conventional HC program.